The Influence of Play Therapy Arranging A Tower of Donut on Improving The Motor Ability of Down Syndrome Children at The Foundation For The Development of Disabled Children (Ypac) Makassar - Sanghati, Sanghati (Journal of Asian-african Focus in Health, 2023)
The aim of this research is to determine the effect of play therapy arranging donut towers on improving the motor skills of children with Down syndrome at the Makassar Foundation for the Development of Disabled Children (YPAC) . The method used in this research is "one group pretest-posttest design", namely a research design This is done by giving a pretest (initial observation). The results of the study showed that before being given play therapy to arrange donut towers ( pretest ), there were 6 children (40.0 % ) who were not yet capable of motor skills. From this research it can be concluded that Play therapy arranging donut towers can influence children's motor development, because this therapy can train hand and eye coordination as well as children's ability to actively move their body parts.